Peran Literasi Multibahasa dalam Penguatan Spiritualitas Generasi Z Penghayat Kepercayaan di Era Globalisasi Bahasa - Nimas Sulistianingsih; Esti Widiyaningsih; Ruwiyati Ruwiyati (Pusat Riset dan Inovasi Nasional, 2026)
The phenomenon of language globalization has brought a significant influence on the communication patterns and cultural identity of Generation Z, including those who adhere to indigenous belief systems. The global trend that emphasizes the dominance of foreign languages often leads to a decline in appreciation for local languages and the spiritual values embedded within them. This article aims to examine the role of multilingual literacy as a means of strengthening the spirituality of Generation Z adherents of indigenous beliefs in facing the challenges of language globalization. The research method used is a literature study by reviewing various theoretical sources and relevant research findings from the past five years. The results indicate that multilingual literacy not only enhances cross-cultural communication skills but also strengthens the spiritual awareness and cultural identity of Generation Z through the preservation of local languages and the interpretation of local values in a modern context. Therefore, multilingual literacy can serve as an effective strategy for developing a generation that is religious, has strong character, and remains rooted in its traditional beliefs amidst the rapid flow of globalization.